Circulating Heparan Sulfate Proteoglycans as Biomarkers in Health and Disease - Lepedda, Antonio Junior; Nieddu, Gabriele; Piperigkou, Zoi; Kyriakopoulou, Konstantina; Karamanos, Nikolaos; Formato, Marilena (Seminars in Thrombosis and Hemostasis, 2021)
Cell-surface heparan sulfate proteoglycans (HSPGs) play key roles in regulating cell behavior, cell signaling, and cell matrix interactions in both physiological and pathological conditions. Their soluble forms from glycocalyx shedding are not merely waste products, but, rather, bioactive molecules, detectable in serum, which may be useful as diagnostic and prognostic markers. In addition, as in the case of glypican-3 in hepatocellular carcinoma, they may be specifically expressed by pathological tissue, representing promising targets for immunotherapy. The primary goal of this comprehensive review is to critically survey the main findings of the clinical data from the last 20 years and provide readers with an overall picture of the diagnostic and prognostic value of circulating HSPGs. Moreover, issues related to the involvement of HSPGs in various pathologies, including cardiovascular disease, thrombosis, diabetes and obesity, kidney disease, cancer, trauma, sepsis, but also multiple sclerosis, preeclampsia, pathologies requiring surgery, pulmonary disease, and others will be discussed.
Keywords: syndecans; glypicans; glycocalyx shedding; circulating HSPGs; disease biomarkers